Internet of things security implementation using blockchain for wireless technology - Karim, Karim Jabur (2019)
Blockchain is a new security system which group many data into a block or so called classifying the data into a block. The block can have many types and each of them content data and security code. By using a decentralize mechanism, one security code protect all the data. That could happen at the server. In this research, a network of wireless sensor technology is proposed. The transmission of sensor data is via the Internet of things (Internet of Thing) technology. As many data transmitted, they have to classified and group them into a block. All the blocks are then send to the central processing unit, like a microcontroller. The block of data is then processed, identified and encrypted before send over the internet network. At the receiver, a GUI or Apps is developed to open and view the data. The Apps or GUI have an encrypted data or security code. User must key in the password before they can view the data. The password used by the end user at the Apps or GUI must be equivalent to the one encrypted at the sensor nodes. This is to satisfy the decentralized concept used in the Blockchain. To demonstrate the Blockchain technology applied to the wireless sensor network, a MATLAB Simulink function is used. The expected results should show a number of block of data in cryptography manner and chain together. The two set of data. Both have the data encrypted using hash. The black dots indicate the data has been encrypted whereas the white dot indicate indicates the data is not encrypted. The half white and half black indicates the data is in progress of encrypted. All this data should arrange in cryptography order and chain together in a vertical line. A protocol called block and chain group the data into the block and then chain then. The data appears in the blocks and send over the network. As seen in the simulation results, the yellow color represents the user data. This data has a default amplitude as 1 or 5. The data is chained and blocked to produce the Blockchain waveform Keywords: Blockchain, Internet of things, Wireless Sensor Network and MATLAB Simulink